α-chloralose poisoning in a cat - Grau-Roma, Llorenç; Stephens, Adam; Wessmann, Annette; Carmichael, Nick; de Brot, Simone (BMJ Publishing Group, 2016)
A five-year-old domestic cat with acute unexplainable neurological signs was presented for postmortem examination. Clinically, the cat showed an acute onset of ataxia, depressed mentation and continuous twitching/ seizure activity in the morning after having been outside overnight. Despite immediate treatment, the cat# progressed within 24 hours to a comatose state, opisthotonus and severe miosis unresponsive to light. Given a poor prognosis, euthanasia was elected. Gross findings were disappointing and consisted of a nonspecific lung oedema and congested lungs and spleen. Surprisingly, within the stomach and intestines, fragments of cockshafers were found. Histological examination confirmed the gross findings and additionally showed evidence of mild brain oedema, but failed to identify a cause for the severe clinical signs. In a final attempt to solve the case, a urine sample was tested for toxic substances and it was found to contain a significant amount of α-chloralose. This finding was unexpected.